Glycemic control in children and adolescents with type 1 diabetes mellitus in post conflict Iraq: a primary report - Kadhim, Dena M.; Al-Kaseer, Eman A.; Al-Zubaidi, Munib A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Type 1 diabetes mellitus (T1DM) is a common disease in childhood. A linear relation between glycemic control (HbA1c < 7) and onset or progression of complication was detected. Only few individuals achieve glycemic control.Objective: To estimate the glycemic control among diabetic children attending tertiary center.Methods: All diabetic children registered in the diabetic consultancy clinic in Children Welfare Teaching hospital (298) were included in the study. Case records were reviewed and information on demography, weight and height, age at diagnosis and HbA1c was requested.Results: Out of the total, 23.8% diabetic children had glycemic control. Glycemic control was decreasing with age (p=0.001), significantly prominent in preschool children (p=0.001), and inversely related with BMI (p=0.03). Sex was not affecting glycemic control.Conclusion: Rate of glycemic control was low. It is poorer in those diagnosed in school age, adolescents and obese children.